Administration of services for the elderly in Chachoengsao Province, Thailand - Jusiri, Sirapop (Vigan City : [s.n.], 2010)
This study was conducted to assess the administrator of services for the elderly under the Local Government Units in Chachoensao Province, Thailand. In addition, administrative capability of Local Government Units, and community participation on the administration of service for the elderly. Moreover, it determined whether the administration of services for the elderly influence the impact. The descriptive-correlational method of research was employed in the study. The data needed in this study were gathered through the use of a questionnaire which was adapted from other researchers. Documentary analysis and interviews during the time of the researcher's visits were likewise utilized in the study. The study covered the Local Government Units in Chachaongsao, Thailand, and the respondents included 231 Local Government Unit administrators, 108 LGU Health Office staff, 231 Health for Elderly Office staff, 240 District Health Center staff, Elderly Club officials, 400 volunteer workers and 1095 elders. In the analysis of data, the following statistical tools were utilized: frequency and percentage, mean, and Multiple Regression Analysis. The findings of the study show that the respondents, composed of LGU administrators, LGU Health Office heads, Health for Elderly Center staff, District Health Center staff, Elderly Club officials, and volunteer workers, were predominantly female, between the ages of 41-50 years, married, bachelor's degree holders, earning a monthly salary of 31, 000-40,000 baht, Buddhists and have worked in the area for 7-9 years.
Bibliography: pages 70-71.
CHED-La Union
Keywords: Elderly